1973
DOI: 10.1002/hlca.19730560510
|View full text |Cite
|
Sign up to set email alerts
|

Homopolar and Heteropolar Bond Dissociation Energies and Heats of Formation of Radicals and Ions in the Gas Phase II. The relationship between structure and bond dissociation in organic molecules

Abstract: Summary. The preceeding paper presents a critical tabular compilation of 2-center homo-and heteropolar bond dissociation energies. This paper deals with some empirically derived general aspects of these data, particularly regarding relationships between structure and reactivity, i.e. substituent effects on bond dissociation energies. 'Extra' stabilization energies generated in electronically delocalized radicals or ions derived from these experimental data are also presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1974
1974
2003
2003

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Figures 2 and 3), indicate an enhanced complexity for the fluorinated analogues. At first sight this might appear to be contrary to what would be expected given that fragmentation processes such as the loss of HF compared with H 2 are effectively thermolytically equivalent [25]. The behavior, and hence prediction, of the mass spectra of polyfluroinated materials, when compared to their hydrocarbon counter parts, appears to be fraught with difficulty.…”
Section: Resultsmentioning
confidence: 87%
“…Figures 2 and 3), indicate an enhanced complexity for the fluorinated analogues. At first sight this might appear to be contrary to what would be expected given that fragmentation processes such as the loss of HF compared with H 2 are effectively thermolytically equivalent [25]. The behavior, and hence prediction, of the mass spectra of polyfluroinated materials, when compared to their hydrocarbon counter parts, appears to be fraught with difficulty.…”
Section: Resultsmentioning
confidence: 87%
“…In case of a homopolar and effectively complete C-H bond breaking in the transition state, a maximum effect of about 12.5 kcalimole from the gain in allylic stabilization energy [15] would be expected for vinyl substituents. To a first approximation it may then be concluded that in the transition state, the C-H-bond is broken to 50% or greater.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to keep in mind that vinylsubstituents are expected to stabilize (via polarizability stabilization [25]) ensuing positive charges on the carbon atom Y [eq. (7)] by about as much [15] as emerging radical sites. A partial heteropolar C-H bond rupture, i.e., a pronounced polar character of the transition state would also be reconcilable with the observed difference in E, of -5 kcal/mole.…”
Section: Discussionmentioning
confidence: 99%
“…3 which illustrates the results of the thermochemical estimates discussed above. The differences between the calculated energies of the isomeric biradicals 21 to 23 arise largely from the different stabilization energies attributed to allylic (Es = 9.6 kcal/mol) and propargylic (E, = 6.5 kcal/mol) resonance [35]. The precursor of 1, biradical21, is calculated to be less stable than 22 and 23.…”
mentioning
confidence: 98%